Student attrition at technical and vocational educational training (TVET) institutions: the case of XCel Technical College in Malaysia - Had Sabtu, Helminiry (Canadian Center of Science and Education, 2016)
Student attrition is a challenging issue for tertiary education institutions, especially Technical and Vocational Education Training (TVET) institutions. There are a lot of explanations why students withdraw from college level programmes and the causes may be unique for students who sign up in a course that suits their interest areas.Small student retention rates reflect negatively on the reputation of the institution and even more, its academic status.This would, in turn, influence institution enrolment, finances, and future plans for development.Thus, this research effort was designed to investigate the influences of students’ withdrawal from these institutions before completion of their studies. As this research took the qualitative approach, data collection was performed through interviews and focus group discussions involving two groups of students (i.e., those who dropped out and those who continued with their studies) from XCel Technical College. The findings showed that the students’ reasons for dropping out from the TVET institutions programme are varied, all which were classified into two categories, namely institutional factors (e.g., training facilities, learning materials, and scheduling) and student characteristics (e.g., parental/family influence and urgency of getting employment).This findings support the results of earlier studies which highlighted that student characteristics, institutional factor, educational and occupational goals and commitments, financial status and other personal factors, are important to their retention in higher education programs (Bafatoom, 2010; Bean, 1980; Braxton, 2005; Pascarella & Terenzini, 1983; Spady, 1970, 1971; Tinto, 1975, 1993).